(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The basic elements of survival of human race is based upon ecological environment, the development of social, economic and the security of the ecological environment are closely interwoven and interact with each other. The environmental infirmity, unswervingly affects the steadiness of the local ecosystem and the sustainable development of the ecological environment. The assessment of regional ecological fragility is a qualitative and quantitative analysis of the uneven allocation of ecological environment factors caused by human socio-economic activities or changes in ecosystems. About 220 years ago the industrial revolution took place– factories came up and things began to be made in bulk, using machines. Machines need energy to run; most of this energy comes from fuels- like coal and oil which are known as fossil fuels. When fossil fuels are burnt, carbon dioxide, methane, ozone, chlorofluorocarbons, nitrous oxide, increased. The gases listed are called Greenhouse Gases (GHGs), over the last 200 years our activities are dumping massive quantities of GHGs into the atmosphere. It is clear; this time around it is humans that are responsible for climate change, hence we are facing a fragile environment. A growing body of research shows that the more people value money, image, classs, status, and positions by personal achievement, the less they care about other living species and the less likely they are to recycle, to turn off lights in unused rooms, and to walk or bicycle to work1. It is high time for a complete and comprehensive examination of the impacts of change in land use, loss of biodiversity, use of fertilizers and pesticides and consistent pollution of air and water bodies. With half the world now living in cities and billions of dollars spent each year on growth and infrastructure, we need to finance and implement sustainable infrastructure practices that reduce our environmental footprint, employ clean technologies and are economically viable. Handprints are needed to save the environment and minimize the pressure or footprints on environment.